E-Services Quality: An Analysis of Customer's Mobile Banking Services in Sharia—A Systematic Literature Review - Nia Kumaladewi; Dede Rosyada; Erma Suryani; Nashrul Hakiem (Applied Information System and Management (AISM), 2025)
In the current digital era, banking services have rapidly evolved thanks to technological advancements, such as mobile banking, which allows customers to conduct transactions easily and efficiently. Studies show that customer perception and satisfaction levels highly depend on service standards, available features, and user experience when using the service. Studies have shown that how customers feel about a service and how satisfied they are with it relies a lot on the quality of the service, the features it offers, and how easy it is to use. A big part of how well financial services on mobile devices do is how good digital services are, particularly in sharia banking that operates in accordance with Sharia principles and regulations. This research aims to gather systematic literature about the level of quality in mobile banking features provided by sharia-compliant banks. To comprehend the connection between customer experience and the effectiveness of e-services in mobile banking apps, the modified e-services quality model is essential. Finding the elements that affect the quality of e-services and consumer happiness, as well as investigating methods for enhancing digital services in compliance with sharia law, are the main goals of this study. It is anticipated that the findings of this study will offer more profound understandings of how Islamic banks may enhance the quality of their mobile banking services.